Pengaruh Sistem Layanan Komputerisasi Stasiun Pengisian Bahan Bakar Umum terhadap Kepuasan dan Loyalitas Konsumen serta Motivasi Membeli Bahan Bakar Minyak di Gerbangkertasusila - Samiatun, Samiatun (Universitas Brawijaya, Indonesia, 2008)
The result of hypothetical test shows that the six hypotheses stated in this research proves its truth or accepted. Subsequently, based on problem statement and hypothetical test result, it can be concluded as the finding of this research as follows. Computerized facility system on gas station has significant influence toward consumer's satisfaction. Computerized facility system on gas station has significant influence toward consumer's loyalty. Computerized facility system on gas station has significant influence toward consumer's motivation to purchase. Consumer's satisfaction has significant influence toward consumer's loyalty. Consumer's satisfaction has significant influence toward consumers motivation to purchase. Consumer's loyalty has significant influence toward consumer's motivation to purchase. Finally, it is formulated a general conclusion which states that computerized facility system on gas station has significant influence toward consumer's motivation to purchase.